Birth Complications and Risk of Cerebral Palsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1987)
Statisticians at the National Institutes of Health (NINCDS), Bethesda, MD have compared the follow-up neurologic status of full-term infants whose birth was complicated but who were free of signs of hypoxic-ischemic encephalopathy (HIE) in the nursery period with asymptomatic infants whose births were uncomplicated.